TEOREMA TITIK TETAP UNTUK PEMETAAN KANNAN PADA RUANG METRIK MODULAR TERITLAK - Harini, Lusi (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2019)
In this paper, we will discuss about fixed point theorems in generalized modular metric space for Kannan-D_λ  type mapping. The existence of the fixed point of this mapping is guaranteed by providing that the mapping domain is a -finite set and the Kannan-D_λ  mapping constant α(0,1/2) satisfied α K<1 where K is a constant from the axiom of generalized modular metric space.